2(3x+1)-(x+2)=0

Simple and best practice solution for 2(3x+1)-(x+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+1)-(x+2)=0 equation:



2(3x+1)-(x+2)=0
We multiply parentheses
6x-(x+2)+2=0
We get rid of parentheses
6x-x-2+2=0
We add all the numbers together, and all the variables
5x=0
x=0/5
x=0

See similar equations:

| -9+7(1+8x)=28 | | x+30=-3x-2 | | 7r+9=-26 | | 9x+15=12x-19 | | (1/3)x-4=3 | | 4*3x-5=6x-2 | | 3*6+x=24 | | 10+7(1+8x)=28 | | 2.2x+3.3=14.3 | | -2x-10=x+40 | | 1x=3x-12 | | 7x-6-3x=22 | | -23=4+5(s+3) | | 2a+9=-5 | | 4b+4=3 | | -x-18=3x+6 | | 9(k+6)+3=7k-10 | | 6(7x+3)=5(3x-4) | | 9(b+5)+11=2 | | 3x²-21x+30=0 | | x+18=72+2x | | 20=7(9f-3) | | 11(n+4)+12=6n-12 | | -7(-6r+14)=-14 | | -4x+-12=12+-4x | | x+(-9)=-14 | | 7=p-74/2 | | 16^2+-10x-27=-6x+5 | | 9=p+2 | | .5s+1=7+4.5s0.5s+1=7+4.5s | | 6.4=6x | | -15=-13x+15;x=5 |

Equations solver categories